Answers

2016-04-07T20:09:17+05:30
Let x be any positive integer. then by euclid's division lemma 
x = 3q ,or 3q + 1, or 3q +2
so, x³ = (3q)³ 
          = 27q³
          = 9(3q³)
          =9m where m = 3q³
similarly, x³ = (3q +1)³
                   = 27q³ + 1³ + 3(3q²)(1) + 3(3q)(1)²
                   = 27q³ + 1 + 27q² + 9q
                   = 27q³ + 27q² + 9q + 1
                   = 9[q(3q² + 3q +1)] + 1
                   = 9m + 1 where m= q(3q² +3q + 1)
again, x³ = (3q +2)³
               = 27q³ + 2³ + 3(3q)²(2) + 3(3q)(2)²
               = 27q³ + 8 + 54q² + 36q
               = 27q³ + 54q² + 36q + 8
               = 9[q(3q² + 6q + 4)] + 8
               = 9m + 8 where m= q(3q² + 6q + 4)
0
deserves to be the brainliest
so plz mark it as the brainliest